Political education regarding concept of nationality in the perception of modernist islamic politics in Indonesia - Putra, Tarekh Febriana; Darmawan, Cecep; Anggraeni, Leni (Universitas Islam Malang, 2023)
The plurality of political perceptions in Indonesia certainly gives rise to a diversity of political understandings. In some situations, this can lead to unexpected extreme political disparities, including those that arise in modern Islamic political thought. Political education as an instrument for unifying the nation's political interests has a strategic role in overcoming this problem. Thus, an objective study is needed to analyze the perceptions of modernist Islamic groups in viewing political and national education. This research was conducted to: 1) find out the perceptions of modernist Islamic political activists in Indonesia about the state; 2) and modernist Islamic political perceptions of political education. The research was conducted on modern Islamic political activists represented by the Regional Leadership Council of Partai Keadilan Sejahtera in Bandung City. This research approach uses a qualitative approach with descriptive methods. Data collection techniques using interviews, observation, and documentation studies. The results of the study show that there is objectification of Islamic political thought in viewing political education to strengthen commitment to the nation.